Pengaruh Pemberian Gelombang Bunyi Jenis Murottal Terhadap Pertumbuhan Batang Dan Daun Pada Pembibitan Kacang Tanah (Arachis Hypogea) - Zulfaniar; Hernawati; Sahara (JFT: Jurnal Fisika dan Terapannya, 2023)
This study aims to determine the effect of murottal type sound waves on stem height, number of leaves and number of stalks on peanut plant growth. Using local peanut seeds with the addition of organic fertilizer, urea fertilizer and without the addition of other nutrients. The peanut seeds were treated with 4000 Hz murottal sound with different exposure times and without murottal sound exposure. Peanut seedlings were observed using a camera to obtain images and using measuring instruments to determine the growth of stems and leaves. The results showed that the difference in the effect of giving sound and without sounding could give a change in the average increase of 6 - 9 cm in stem height, the number of leaves experienced an average increase of 4 leaves while the change in the number of stalks experienced an increase of 1 stalk.